Communicative Competence of Teachers as Base of Successful Pedagogical Communication - Aukštkalnytė, Dėja (Acta Paedagogica Vilnensia, 1999)
The author of this article tries to explain the essence of pedagogical communicating analysing works of many contemporary scientists. Conclusion is that pedagogical communication is communicative process between the teacher and the student, perception of one another and interaction. In the article the author says that communicative competence is an important condition of pedagogical communication. The model of communicative competence explains its links with communicative skills. Communicative skills are grouped, as many authors conclude, in verbal and nonverbal behaviour. The final part ends with the conclusions about the importance to improve communicative skills of the future teachers.